Community-Based Mobile Self-Assessment for Tuberculosis Screening Among Parents and Children: A Cross-Sectional Study - Warastuti, Widya; Sulistyowati, Reny; Ariestini, Tri Ratna (Journal of Applied Nursing and Health, 2026)
Background: Conventional tuberculosis screening is often limited by reporting delays and low accessibility. This study evaluates a digital solution to address this gap by integrating behavioral assessment and screening of two populations into a single community-based platform. The study aimed to evaluate the NOR TBC mobile app in identifying suspected tuberculosis cases and analyze the relationship between cognitive factors and preventive behaviors. Methods: This cross-sectional observational study followed STROBE guidelines. Using convenience sampling, 70 parents, were recruited. Data were collected via the app’s integrated modules for Knowledge, Attitude, and Practice and self-screening. App quality was validated using ISO 25010 and expert review. Data were analyzed using descriptive statistics and Chi-Square tests (p < 0.05). Results: The NOR TBC mobile identified 5.7% adult and 14.3% child presumptive TB cases. Technical evaluation rated the app as "Good" (76.67%), with expert validation confirming it as "Very Feasible" (60%) and "Feasible" (40%). Most respondents exhibited good knowledge (58.6%), positive attitudes (94.3%), and favorable behaviors (82.9%). Chi-square analysis showed significant associations: respondents with good knowledge were 4.2 times more likely to engage in tuberculosis prevention (p=0.012; OR=4.2), and those with positive attitudes had 3.8 times higher odds of favorable behavior (p=0.034; OR=3.8). Conclusion: The NOR TBC mobile application demonstrates strategic potential in strengthening community-level tuberculosis detection and improving health literacy. This digital innovation reaches vulnerable populations that may be missed by conventional surveillance. Further development and controlled trials are recommended to evaluate long-term effectiveness